Albumin liver dialysis as pregnancy-saving procedure in cholestatic liver disease and intractable pruritus - Lemoine, Maud (The WJG Press and Baishideng, 2008)
Progressive familial intrahepatic cholestasis type 3 (PFIC3) is a rare cholestatic liver disease. Such liver disease can get worse by female hormone disorder. Albumin dialysis or Molecular Adsorbent Recirculating System (MARS) has been reported to reverse severe cholestasis-linked pruritus. Here, we report the first use of MARS during a spontaneous pregnancy and its successful outcome in a patient with PFIC3 and intractable pruritus. Albumin dialysis could be considered as a pregnancy-saving procedure in pregnant women with severe cholestasis and refractory pruritus.